Focusing on the brighter side of Sevoflurane: Realizing true potential of an anesthetic agent as a regulator of cell signaling pathways and microRNAs in different cancers - Qureshi, Muhammad Zahid; Attar, Rukset; Javed, Anam; Sabitaliyevich, Uteuliyev Yerzhan; Adylova, Aima; Konysbayevna, Konysbayeva Kenzhekul; Buha, Aleksandra; Sohail, Muhammad Imran; Aras, Aliye (Cellular and Molecular Biology, 2019)
Reconceptualization of different anesthetics as anticancer agents has opened new horizons for a better and sharper analysis of true potential of Sevoflurane as a promising and frontline candidate in the pipeline of anticancer agents. Sevoflurane mediated regulation of cell signaling pathways and non-coding RNAs has leveraged our understanding to another level. There have been remarkable advancements in unraveling mechanistic insights related to the ability of sevoflurane to modulate microRNAs in different cancers. Astonishingly, sevoflurane mediated regulation of miRNAs and long non-coding RNAs have been more comprehensively addressed in ischemia-reperfusion injuries. However, researchers yet have to gather missing pieces of premium research-work to uncover mechanistic regulation of long non-coding RNAs by sevoflurane in various cancers. Sevoflurane modulated control of miRNAs have been reported in glioma, colorectal cancer, breast cancer and hepatocellular carcinoma. In this review we have attempted to summarize most recent cutting edge and high-impact experimental researches which have elucidated myriad of underlying mechanisms modulated by sevoflurane to inhibit cancer development and progression. Despite some of the amazing pharmacological properties of sevoflurane, it has been shown to possess darker side because of its involvement in positive regulation of metastasis. In accordance with this notion we have also summarized how sevoflurane enhanced migratory potential of different cancer cells in a separate section. Therefore, these aspects have to be tested in better designed experimental models to identify most relevant types of cancers which can be therapeutically targeted by sevoflurane.